Synergistic Effect of Dual Particle-Size AuNPs on TiO(2) for Efficient Photocatalytic Hydrogen Evolution - Zhao, Qian (Nanomaterials (Basel), 2019)
Design of efficient catalysts for photocatalytic water-splitting hydrogen evolution is of fundamental importance for the production of sustainable clean energy. In this study, a dual particle-size AuNPs/TiO(2) composite containing both small (16.9 ± 5.5 nm) and large (45.0 ± 9.8 nm) AuNPs was synthesized by annealing two different sized AuNPs onto TiO(2) nanosheets. Dual particle-size AuNPs/TiO(2) composites of 2.1 wt% catalyze photocatalytic H(2) evolution 281 times faster than pure TiO(2). Control experiments indicate the observed rate increase for the 2.1 wt% dual particle-size AuNPs/TiO(2) composites is larger than 2.1 wt% small AuNPs/TiO(2) composites, or 2.1 wt% large AuNPs/TiO(2) composites in isolation. The observed photocatalytic enhancement can be attributed to the synergistic effect of dual particle-size AuNPs on TiO(2). Specifically, small-sized AuNPs can act as an electron sink to generate more electron-hole pairs, while the surface plasmon resonance (SPR) effect of large-sized AuNPs concurrently injects hot electrons into the TiO(2) conduction band to enhance charge transfer. In addition, a gold-dicyanodiamine composite (GDC)-directed synthesis of 2.1 wt% dual particle-size AuNPs/TiO(2) composites was also completed. Notably, a photocatalytic efficiency enhancement was observed that was comparable to the previously prepared 2.1 wt% dual particle-size AuNPs/TiO(2) composites. Taken together, the synergistic effects of dual particle-size AuNPs on TiO(2) can be potentially used as a foundation to develop semiconductor photocatalyst heterojunction with enhanced photocatalytic activity.